Bibliometric Analysis of University Social Responsibility: Advancing Transparency and Sustainability in Higher Education - Yuni Ekawarti; Mohamad Adam; Yusnaini Yusnaini; Hasni Yusrianti (Jurnal Ilmiah Akuntansi, 2024)
While the importance of University Social Responsibility (USR) is widely acknowledged in academic discourse, there remain substantial gaps in understanding how it interacts with sustainability, especially in terms of transparency as a measurable outcome. This study specifically addresses these gaps by employing bibliometric analysis to comprehensively explore the scope of literature on 'University Social Responsibility,' establishing it as a crucial transparency indicator for sustainability practices in higher education institutions. Using the VOSviewer tool, data from 356 scientific articles, published between 2006 and 2023 and sourced from Scopus, were meticulously analyzed. This analysis elucidates the relationships between authors, journals, and keywords, providing fresh insights into the evolving research landscape. These insights identify emerging trends that link USR to sustainability initiatives in higher education and elucidate the relationship between USR and transparency in achieving sustainability goals. The findings offer valuable insights for researchers and policymakers, underscoring the importance of transparency-based USR practices in promoting sustainable development.